Time heterogeneity of the Förster radius from dipole orientational dynamics impacts single-molecule Förster resonance energy transfer experiments - David Frost; Keisha Cook; Hugo Sanabria (Physical Review Research)
Förster resonance energy transfer (FRET) is a quantum mechanical process governing the nonradiative energy transfer between coupled electric dipoles. Its strong distance dependence makes it a widely used as a “molecular ruler” in biology, chemistry, and physics. In single-molecule FRET (smFRET) experiments employing time-resolved confocal microscopy, deviations from the theoretical Förster relationship between FRET efficiency and donor fluorescence lifetime—termed dynamic shifts—provide insight into underlying molecular conformational dynamics. A key challenge in interpreting these shifts is disentangling contributions from the intrinsic motion of the fluorescent dyes from those of the biomolecular system under study. We present a novel theoretical framework based on Langevin dynamics to model the stochastic translational and rotational motion of dye linkers, incorporating first-principles physics and chemical constraints consistent with molecular dynamics simulations. Our results demonstrate that the dominant factor influencing dynamic shifts in smFRET is the relative orientational fluctuations of the dyes' electric dipole moments, rather than their accessible spatial volumes. These findings refine the theoretical foundations of FRET and provide the most precise estimates of FRET efficiency to date, enhancing its utility as a molecular-scale probe of dynamic processes.